Fundamentals of Software Engineering 5th International Conference, FSEN 2013, Tehran, Iran, April 24-26, 2013, Revised Selected Papers - Arbab, Farhad; Sirjani, Marjan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 5th IPM International Conference on Fundamentals of Software Engineering, FSEN 2013, held in Tehran, Iran, in April 2013. The 17 full papers presented in this volume were carefully reviewed and selected from 65 submissions. The topics of interest in FSEN span over all aspects of formal methods, especially those related to advancing the application of formal methods in software industry and promoting their integration with practical engineering techniques.
Unbounded Allocation in Bounded Heaps -- On the Complexity of Adding Convergence -- Deadlock Checking by Data Race Detection -- Delta Modeling and Model Checking of Product Families -- Lending Petri Nets and Contracts -- On Efficiency Preorders -- Compiling Cooperative Task Management to Continuations -- Extending UPPAAL for the Modeling and Verification of Dynamic Real-Time Systems -- Efficient Operational Semantics for EB3 for Verification of Temporal Properties -- Interval Soundness of Resource-Constrained Workflow Nets: Decidability and Repair -- Statistical Model Checking of a Clock Synchronization Protocol for Sensor Networks -- A New Representation of Two-Dimensional Patterns and Applications to Interactive Programming -- Push-Down Automata with Gap-Order Constraints -- Model Checking MANETs with Arbitrary Mobility -- Validating SCTP Simultaneous Open Procedure -- Improving Time Bounded Reachability Computations in Interactive Markov Chains -- Checking Compatibility of Web Services Behaviorally.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Logics and Meanings of Programs; Software Engineering